The Influence of Social Media in Increasing Student Motivation in Mathematics Lessons for Elementary Schools - Nursyam, Aisyah; Widyatiningtyas, Reviandari; Palayukan, Hersiyati; Fawait, Aldi Bastiatul (Journal of Social Science Utilizing Technology, 2024)
Background. Mathematics learning in elementary schools (SD) often requires innovative approaches to increase student engagement. With the development of technology, the use of social media as a learning tool is starting to become the focus of research to increase students' learning motivation in mathematics. Purpose. The research aims to measure how much influence the use of social media has in increasing students' motivation in learning mathematics in elementary school, as well as providing a concrete understanding of the relationship between social media and motivation to learn mathematics. Method. A quantitative approach using a survey model is used to examine the impact of social media on student motivation. Questionnaires were distributed to elementary school teachers and mathematics education students via Google Form and WhatsApp (WA) groups. Research ethical principles were upheld, and data were analyzed using Miles and Huberman's qualitative data analysis techniques. Results. The majority of respondents gave a positive view of the influence of social media in mathematics learning. However, there are a small number who feel that social media can interfere with studying concentration. The integration of social media needs to be considered wisely to minimize risks and maximize its benefits in mathematics learning. Conclusion. The research results show that social media has great potential in increasing students' motivation in learning mathematics in elementary school. However, its use needs to be managed wisely and responsive to student needs and preferences. Social media integration can be an interesting and effective learning alternative in the context of mathematics learning at school.